Administrative Unit Proliferation Through Spatial Interaction Approach: Case Study of Lembang City Region - Lili Somantri; Iqbal Eko Noviandi; Agil Akbar Fahrezi; Muhammad Arrafi (Journal of Regional and City Planning, 2023)
Administrative unit proliferation is a decision that needs to be taken based on several considerations based on research. The proposed Lembang City region is an area that will develop into a city in the next few years. For this reason, this research attempted to evaluate the proposed area’s ability to become an administrative city using various spatial aspects. The analytical approaches used in this study were: spatial interaction analysis, which helps to determine the regional economic center; thematic overview analysis, implementing village SDGs through a spatial analysis approach; and SWOT analysis to identify Lembang City region’s strengths, weaknesses, opportunities, and threats in qualitative terms. The study results show that the proposed Lembang City area has excellent potential as a city region. Through a spatial analysis approach supported by geographic information system tools, this research was conducted as a consideration in deciding to expand Lembang Regency may provide significant assistance to the government in its work related to this decision.